Use of Force Preferences and Perceived Effectiveness of Actions Among Crisis Intervention Team (CIT) Police Officers and Non-CIT Officers in an Escalating Psychiatric Crisis Involving a Subject With Schizophrenia - Compton, Michael T.; Demir Neubert, Berivan N.; Broussard, Beth; McGriff, Joanne A.; Morgan, Rhiannon; Oliva, Janet R. (Schizophrenia bulletin, 2011)
Background: Few studies have examined police officers' use of force toward individuals with schizophrenia, despite the widely disseminated Crisis Intervention Team (CIT) model of partnership between mental health and law enforcement that seeks to reduce use of force and enhance safety of officers and individuals with mental illnesses. This study tested the hypotheses that CIT-trained officers would select a lower level of force, identify nonphysical actions as more effective, and perceive physical force as less effective in an escalating psychiatric crisis, compared with non-CIT-trained officers. Methods: Police officers (n = 135)-48 CIT trained and 87 non-CIT trained-completed a survey containing 3 scenario-based vignettes depicting an escalating situation involving a subject with psychosis. Data were analyzed using repeated-measures analyses of variance. Results: Officers escalated their preferred actions across the scenarios. A significant scenario by group interaction indicated that CIT-trained officers chose less escalation (ie, opting for less force at the third scenario) than non-CIT-trained officers. Officers reported decreasing perceived effectiveness of nonphysical action across the 3 scenarios. A significant scenario by group interaction indicated that CIT-trained officers reported a lesser decline in perceived effectiveness of nonphysical actions at the third scenario. CIT-trained officers consistently endorsed lower perceived effectiveness of physical force. Conclusions: Efforts are needed to reduce use of force toward individuals with psychotic disorders. These findings suggest that CIT may be an effective approach. In addition to clinical and programmatic implications, such findings demonstrate a role for clinicians, advocates, and schizophrenia researchers in promoting social justice through partnerships with diverse social sectors.